An anion sensor based on an organic field effect transistor1. Issue 46 (11th June 2015) - Minami, Tsuyoshi; Minamiki, Tsukuru; Tokito, Shizuo
<x xml:space="preserve">Abstract</x> An OFET sensor device possessing an anion receptor was able to electrically detect basic anion species in water, meaning that OFETs can effectively read out anion recognition behaviour of supramolecular receptors.